Kebertahanan Undha Usuking Basa pada Kalangan Remaja di Desa Plipiran, Jawa Tengah - Utami, Novi Elistya; Suwena, I Wayan; Sama, I Nyoman (Department of Anthropology Udayana University, 2024)
The Javanese language is a means of communication for the Javanese people which contains cultural values ??that can reflect the character of the speakers. Undha Usuking Basa or also known as unggah ungguh base is a level of speech in Javanese that is used to regulate the behavior patterns of the people. Nowadays, the Javanese language upload has decreased, especially among teenagers. From this phenomenon, two main problems can be drawn, namely (1) The attitude of adolescents towards survival is really high in the current era (2) Aspects that cause a decrease in the quality of the use of upload guh in teenage speakers. The theory used is symbolic interaction theory and semiotic theory. This study used a qualitative approach with a descriptive-qualitative type of research. Data collection techniques using observation techniques, interviews, and literature study. The results of the study reveal that there is a lack of concern for adolescents as the younger generation regarding the importance of preserving upload-ungguh for adolescents as well as the aspects underlying the decline in upload-ungguh namely internal aspects and external aspects.